2004
DOI: 10.1128/jvi.78.2.585-594.2004
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Ligand 10 Controls Viral Infection in the Central Nervous System: Evidence for a Role in Innate Immune Response through Recruitment and Activation of Natural Killer Cells

Abstract: The CXC chemokine ligand 10 (CXCL10) is a non-ELR CXC chemokine that exerts a potent chemotactic effect on activated T cells through binding the receptor CXCR3 (5). CXCL10 is expressed within tissues following viral infection, suggesting an important role for this chemokine in host defense by contributing to lymphocyte activation, extravasation, and accumulation of virus-specific T cells within sites of infection. Indeed, recent studies with antibody-mediated targeting of CXCL10 and CXCL10 Ϫ/Ϫ mice demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 38 publications
8
103
2
Order By: Relevance
“…MHV infection of astrocytes results in robust expression of CXCL10 that is most likely controlled by type I IFN expression and not by cytokines and/or chemokines derived from infiltrating T cells such as IFN-␥ and CCL5, respectively. Moreover, MHV infection of the CNS of RAG1 Ϫ/Ϫ mice (lacking T and B cells) results in robust expression of CXCL10 by astrocytes, which further supports the fact that expression of this chemokine is not dependent on factors generated from infiltrating T cells (52).…”
Section: Discussionsupporting
confidence: 58%
“…MHV infection of astrocytes results in robust expression of CXCL10 that is most likely controlled by type I IFN expression and not by cytokines and/or chemokines derived from infiltrating T cells such as IFN-␥ and CCL5, respectively. Moreover, MHV infection of the CNS of RAG1 Ϫ/Ϫ mice (lacking T and B cells) results in robust expression of CXCL10 by astrocytes, which further supports the fact that expression of this chemokine is not dependent on factors generated from infiltrating T cells (52).…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have reported positive [15,16] and negative [17,18] consequences linked to CXCL10 or CXCR3 expression during infection or autoimmune disease implying the role of CXCR3 and its ligands may be tissue-and pathogen-specific.…”
Section: Introductionmentioning
confidence: 99%
“…In pathological conditions, the integrity of the BBB and the BCSFB can be disturbed, becoming permissive for the entry of inflammatory cells. Among them, NK cells were shown to be recruited to the CNS following several pathological conditions (2)(3)(4)(5)(6).…”
Section: Nk Cells In Central Nervous System Disordersmentioning
confidence: 99%
“…Nonetheless, their mode of entry into CNS and the molecules leading to this recruitment are poorly understood. This recruitment could be coordinated by CNS resident cells, such as microglia, astrocytes, and neurons, that secrete chemokines involved in NK cell migration, such as CCL2, CXCL10, and CX3CL1 (3,18,38) .…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%